PENGARUH UKURAN PERUSAHAAN, METODE AKUNTANSI, DAN STRUKTUR KEPEMILIKAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013 - Edeline Edeline; Amelia Sandra (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
Tax is one source of country’s revenue comes from the people. Efforts in this country instead of optimizing revenues is not without obstacles. The main obstacle in the context of state income tax in this sector is tax avoidance. The purpose of this research is to examine if firm size, accounting method, and ownership structure have an influence on tax avoidance in manufacturing companies listed in Indonesia Stock Exchange in period 2010-2013. This study uses observational methods on secondary data which obtained from the annual financial report and audited financial statements of companies. This study uses 27 manufacturing companies that listed in Indonesian Stock Exchange as a sample. This research uses purposive sampling method for sampling method. The analytical method used is Structural Equation Modelling (SEM) using a variance-based Partial Least Square (PLS). The results showed that firm size has a value of T-statistic for 2.521 where the value is greater than 1.96, accounting method has a value of T-statistic for 4.015 where the value is greater than 1.96, and ownership structure has a value of T-statistic for 1.759 where the value is smaller than 1.96. From the results of this study concluded that firm size and the accounting method have influence on tax avoidance. While the ownership structure found no effect on tax avoidance.